Implementasi Kurikulum Merdeka dalam Membangun Citra Unggul Sekolah Dasar: Studi Kasus di SDN Pasar Lama 1 Banjarmasin - Meldy Nursyalima; Yuliasari Yuliasari; Norhayat Norhayat; Nova Fitria; Laila Salatiah; Aslamiah Aslamiah; Diani Ayu Pratiwi (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The implementation of the Merdeka Curriculum has become an important strategy in improving educational quality and strengthening school identity. This study aims to evaluate the implementation of the Merdeka Curriculum in fostering a positive school image at SDN Pasar Lama 1 Banjarmasin. This study employed a descriptive qualitative approach involving the principal, fifth-grade teachers, students, and parents at SDN Pasar Lama 1 Banjarmasin. Data were collected through semi-structured interviews and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings reveal that the implementation of the Merdeka Curriculum contributes to strengthening the school’s image through school culture and character-building programs. These programs focus on developing students’ religious values, discipline, environmental awareness, literacy skills, and self-confidence. The implementation is supported by teachers’ exemplary behavior, principal leadership, and collaboration with parents. The study concludes that the implementation of the Merdeka Curriculum plays a significant role in strengthening school identity and fostering a positive public image.